Intervención psicológica grupal para potenciar las capacidades resilientes en mujeres de 20 a 66 años de edad, víctimas de violencia intrafamiliar del Centro de Equidad y Justicia de Quitumbe en el periodo marzo – julio del 2018 - Constante Morales, Katherine Lizeth (2018)
This systematization has as its main objective the strengthening of the resilient capacities in women who have been victims of domestic violence and those who have been users of the services of the center of Equity and Justice of Quitumbe through a psychological intervention group formed by ten participants, between the age of 20 to 66, from march to July 2018. The methodology used in this work was mixed type using qualitative and quantitative methods. For the information compilation field diaries and participant observations were applied, the categories considered were: self-esteem, relationship skills and independence. With these pillars of resilience, the recognition and resignification of their experiences were achieved along with the empowerment of their capacities. Finally, a series of conclusions are presented to show the achievements of the psychotherapeutic group, and they are evident in the group level and individual level of the purpose of understanding the scope of this work, also several recommendations are presented that should be taken into consideration for the subsequent intervention of actions in favor of the people whose rights have been violated.